VO2 Kinetics during exercise performed at critical power in cyclists and untrained individuals - Caritá, Renato Aparecido Corrêa [UNESP]; Greco, Camila Coelho [UNESP]; Filho, Dalton Müller Pessôa [UNESP] (FapUNIFESP (SciELO), 2013)
The objective was to analyze the oxygen uptake (VO2) kinetics during exercise performed at critical power (CP) in subjects with different aerobic status in cycling. Six trained cyclists (GT) and seven non-trained subjects (GNT) underwent to the following protocols in cyclergometer: (a) incremental to exhaustion to determine VO2max and its respective workload (IVO2max); b) three square-wave tests to exhaustion at 95-110% IVO2max to determine CP, and; (c) one square-wave test to exhaustion at 100%CP. During the exercise at CP the slow component expressed as absolute value (GT: 342.4±165.8 ml.min-1 vs. GNT: 571.3±170.1 ml.min-1) and as the relative contribution to the increase of VO2 during exercise (GT: 10.0±4.6% vs. GNT: 26.6±7.3%) were lower for trained subjects. The VO2 at the end of the exercise at PC (GT: 89.8±8.4%VO2max vs. GNT: 97.4±2.8%VO2max) was significantly lower in GT (σ = 0.045), and similar to VO2max in GNT. Therefore, the aerobic level might influence the VO2 responses to exercise at PC.
Cinética do VO2 durante o exercício realizado na potência crítica em ciclistas e indivíduos não-treinados no ciclismo
Keywords: Aerobic fitness; Cyclists; Heavy exercise